Expression and Regulation of pde6h by Thyroid Hormone During Metamorphosis in Paralichthys olivaceus - Cheng, Yuejuan; Xu, Jiaqian; Fu, Yuanshuai; He, Nisha (Frontiers in Physiology, 2020)
PDE6H is a cone cell-specific inhibitory subunit that plays a critical role in the adaptation of the photosensitive system to bright and dark phases of the light environment. Thyroid hormone (TH) is one of the most important factors that controls development and metabolism in animals, composed mainly of triiodothyronine (T3) and thyroxine (T4). TH also plays a key role in metamorphosis of the flounder (Paralichthys olivaceus), wherein exogenous TH can accelerate the behavioral changes of larvae from the pelagic to benthic type, accompanied by changes in the light environment from bright to dark. In this study, transcriptional analysis showed that pde6h was expression in adult eye, its expression peaks at the climax of metamorphosis, and can be significantly up-regulated to the highest level by exogenous T4 in the early stages of metamorphosis, while being inhibited by thiourea (TU). The rescue experiment showed that metamorphic inhibition of larvae and expression inhibition of pde6h gene in TU groups can be rescued by removed TU. Further, dual-luciferase reporter assay indicated the putative regulatory effect of TH on pde6h expression, mediated directly on the gene promoter by the TRαA gene. Together, we speculated that TH may control physiological adaptation of photosensitive system to light changes during metamorphosis by acting directly on pde6h. This study can help us further study the physiological function of pde6h during flounder metamorphosis in the future.